Circulating activin A is a novel prognostic biomarker in malignant pleural mesothelioma – A multi-institutional study. (August 2016) - Hoda, Mir Alireza; Dong, Yawen; Rozsas, Anita; Klikovits, Thomas; Laszlo, Viktoria; Ghanim, Bahil; Stockhammer, Paul; Ozsvar, Judit; Jakopovic, Marko; Samarzija, Miroslav; Brcic, Luka; Bendek, Matyas; et al.
Abstract: Introduction: The deregulation of activin expression is often observed in various malignancies. Previous studies indicate that activin A plays a protumourigenic role in malignant pleural mesothelioma (MPM). The aim of the study was to evaluate circulating activin A level as a biomarker in MPM. Methods: Plasma samples were collected from 129 MPM patients in four institutions at the time of diagnosis or before surgical resection. Samples from 45 healthy individuals and from 16 patients with non-malignant pleural diseases served as controls. Circulating activin A was measured by enzyme-linked immunosorbent assay and correlated to clinicopathological variables. Results: Plasma activin A level was significantly elevated in MPM patients (862 ± 83 pg/ml) when compared to healthy controls (391 ± 21 pg/ml; P  < 0.0001). Patients with pleuritis or fibrosis only showed a modest increase (versus controls; 625 ± 95 pg/ml; P  = 0.0067). Sarcomatoid (n = 10, 1629 ± 202 pg/ml, P  = 0.0019) and biphasic (n = 23, 1164 ± 233 pg/ml, P  = 0.0188) morphology were associated with high activin A levels when compared to epithelioid histology (n = 94, 712 ± 75 pg/ml). The tumour volume showed a positive correlation with increased circulating activin A levels. MPM patients with below median activin A levels had a significantly longer overall survival when compared to those with high activin A levels (median survival 735 versus 365 d, P  < 0.0001). Importantly, circulating activin A levels were exclusively prognostic in epithelioid MPM. Conclusions: Our findings suggest that the measurement of circulating activin A may support the histological classification of MPM and at the same time help to identify epithelioid MPM patients with poor prognosis. Highlights: Plasma activin A levels are increased in malignant pleural mesothelioma (MPM) patients. Increased levels associated with non-epithelioid morphology and high tumour volume. Plasma activin A level was an independent prognostic factor in MPM patients below 66 years of age with an epithelioid histology.